Global climate change : economic dimensions of a cooperative international policy response beyond 2000. - Australian Bureau of Agricultural and Resource Economics; Australia. Economic and Trade Development Division (Canberra, A.C.T. : ABARE, 1995)
The underlying premise of this study is that the potential risks of global warming are too great to avoid taking further action. Reflecting widespread concerns about climate change, the great majority of governments around the world have chosen to become parties to the United Nations Framework Convention on Climate Change. Governments and community and business groups working through the framework convention have a responsibility to develop effective and equitable global responses to those risks. Economic analysis is important in developing strategies to mitigate climate change that are aimed at achieving key environmental objectives in the medium to long term. The purpose of this report is to assess the economic implications of a range of international abatement strategies and to identify the most cost effective approaches to achieve given environmental objectives.
1. Introduction -- 1.1. International response to climate change -- 1.2. Analysis of policy options to address climate change -- 1.3. Organisation of the report -- 2. International negotiations on climate change -- 2.1. Negotiation of the convention -- 2.2. Negotiations to implement the convention -- 3. Business-as-usual projections -- 3.1. Project emissions -- 3.2. Factors underlying emissions growth -- 3.3. Conclusions -- 4. Impacts and limitations of stabilisation policies -- 4.1. Policy modelling -- 4.2. Multilateral 2000 stabilisation scenario: impact on emissions -- 4.3. Multilateral 2000 stabilisation scenario: impact of welfare -- 4.4. Multilateral 2000 stabilisation plus 20 per cent reduction scenario -- 4.5. Limitations of the analysis -- 4.6. Conclusions - 5. Policies to promote equity -- 5.1. Equity in the framework convention and national responses -- 5.2. Principles of equity -- 5.3. Analysis of various equity rules -- 5.4. Results -- 5.5. Embodied emissions -- 6. Joint implementation to promot efficiency -- 6.1. Forms of joint implementation -- 6.2. Practical aspects of joint implementation -- 6.3. Simulation: overview -- 6.4. Conclusions -- 7. Tradable quotas -- 7.1. Cost minimisation -- 7.2. Compliance costs -- 7.3. Steps to a global tradable quota scheme -- 7.4. Simulation results -- 7.5. Conclusions -- 8. Conclusions -- 8.1. Business-as-usual emissions -- 8.2. Stabilisation policies in select Annex I countries -- Moving to better policies -- 8.4. Further research as a basis for policy -- 8.5. Sime implications for further international action -- appendix A. Description of MEGABARE -- appendix B. Developed country approaches to returning emissions to 1990 levels to 2000 -- appendix C. Detailed results for the stabilisation scenario -- appendix D. Sensitivity analysis -- appendix E. Equity issues associated with a tradable emission quota schemes
"The views expressed in this joint research report are solely those of ABARE and individual officers in the Economic and Trade Development Division of the Department of Foreign Affairs and Trade".
Bibliography: p. 190-197.
Keywords: United Nations Framework Convention on Climate Change -- (1992); Agriculture -- Economic aspects; Climatic changes -- Economic aspects; Climatic changes -- Government policy; Forests and forestry -- Economic aspects; Global warming -- Government policy; Greenhouse effect, Atmospheric -- Economic aspects; Greenhouse effect, Atmospheric -- Government policy; Greenhouse gases -- Environmental aspects